Screening of BHK-21 cellular proteins that interact with outer membrane protein 43K OMP of Fusobacterium necrophorum. (June 2020) - He, Xianjing; Wang, Lina; Li, He; Zhang, Siyao; Wang, Zhihui; Jiang, Jiancheng; Xiao, Jiawei; Wang, Fengfeng; Jiang, Kai; Zhao, Pengyu; Zhang, Aihui; Bi, Lan; et al.
Abstract: Fusobacterium necrophorum is a Gram negative, spore-free, anaerobic bacterium that can cause pyogenic and necrotic infections in animals and humans. It is a major bovine pathogen and causes hepatic abscesses, foot rot, and necrotic laryngitis. The 43K OMP of F. necrophorum is an outer membrane protein with molecular weight of 43 kDa, exhibiting similarity to pore-forming proteins of other Fusobacterium species that plays an important role in bacterial infections. However, the role of 43K OMP in F. necrophorum adhesion remains unknown. In this study, we evaluated whether the 43K OMP of F. necrophorum mediates adhesion to BHK-21 cells and performed a preliminary screen of the proteins that interact with 43K OMP of F. necrophorum by immunoprecipitation-mass spectrometry. The results showed that the natural 43K OMP and recombinant 43K OMP could bind to BHK-21 cells, and preincubation of F. necrophorum with an antibody against the recombinant 43K OMP of F. necrophorum decreased binding to BHK-21 cells. Seventy differential interacting proteins were successfully screened by immunoprecipitation-mass spectrometry. Among these seventy differential interacting proteins, seven cell membrane proteins and four extracellular matrix proteins shown to be relevant to bacteria adhesion through subcellular localization and single-molecule function analysis. These data increase our understanding of the pathogenesis of F. necrophorum and provide a new theoretical basis for the design of antimicrobial drugs against F. necrophorum . Highlights: The 43K OMP mediates F. necrophorum adherence to BHK-21 cells. Eleven proteins may play a potential role in the adherence of F. necrophorum .